Pengaruh Kualitas Pelayanan Jasa Keagenan Kapal dan Komunikasi Interpersonal Terhadap Kepuasan dan Loyalitas Pelanggan Pada Perusahaan Pelayaran PT. Hasnur Internasional Shipping Tbk - Rabiatul Adawiyah; Taharuddin (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2024)
Abstract: This research, focuses on examining the direct and indirect effects of Agency Service Quality and Interpersonal Communication on Customer Satisfaction and Loyalty in the shipping industry, specifically at PT Hasnur International Shipping Tbk. The study employs a quantitative research method with an explanatory type. The population comprises customers of PT Hasnur International Shipping Tbk, including ship owners and management/employees. Data collection is carried out through questionnaires, and the analysis is conducted using SmartPLS Structural Equation Modeling (SEM). The findings of the research demonstrate that Service Quality significantly influences Customer Satisfaction, while Interpersonal Communication has a non-significant impact on Customer Satisfaction. Furthermore, Customer Satisfaction has a significant influence on Customer Loyalty Keywords: Service Quality, Ship Agency Services, Interpersonal Communication, Customer Satisfaction, Customer Loyalty, Shipping Companies